IMPLEMENTASI SISTEM INFORMASI MANAJEMEN DI SEKOLAH MENENGAH KEJURUAN (SMK) MUHAMMADIYAH 1 PADANG - Utama, Hendri Budi; Wachidi, Wachidi; Somantri, Manap (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2019)
Technological advances will be very useful and meaningful to life if used properly and properly. One of the uses of technology in the field of education is in the management information system (SIM). Padang Muhammadiyah 1 Vocational School has made use of these technological advancements to support the smoothness and progress of education with the implementation of management information systems. This has been proven by web / sisfo Â assessment, attendance and report card management. The management information system has been computerized and well-automated, to improve work effectiveness and efficiency. Reducing the use of paper and ink. Then the most important thing is tidying up and securing the data. Data can be input, accessed, and printed anytime anywhere as long as there is an internet connection, can be accessed via a computer and smartphone (Android).